Knowledge and practices related to antibiotic use among women in Malang, Indonesia - Yunita, Sendi Lia; Yang, Hui-Wen; Chen, Yi-Chun; Kao, Li-Ting; Lu, Yi-Zi; Wen, Yuan-Liang; To, Sheng-Yin; Huang, Ya-Li (Frontiers in Pharmacology, 2022)
Background: Antimicrobial resistance is a public health problem that threatens the efficacy of antibiotics. Incorrect knowledge of antibiotics may lead to their inappropriate use, hinder their effectiveness, and cause antibiotic resistance. Population-based educational campaigns have been found to have either mixed or no effect on improving knowledge and appropriate antibiotic practices, suggesting the need for more targeted approaches in tailoring education for specific subpopulations. Women are the primary caregivers of their families and are more willing to contact healthcare providers. They had greater knowledge of antibiotics and better adherence to the completion of the antibiotic regimen. Therefore, they are suitable for prioritization in a campaign program. Objective: This study examined the knowledge and practices of female visitors to health centers in Malang, Indonesia with respect to antibiotic use. Methods: This cross-sectional study was conducted in Malang, Indonesia, in July and August 2018. Data were collected from 677 women. Multivariate logistic regression was performed to identify the potential factors associated with antibiotic knowledge, self-medication, and completion of antibiotic regimens. Results: Overall, 82.7% of respondents were aware that antibiotics are used against bacteria, while 38.4% reported self-medication with antibiotics and 51.7% reported completing antibiotic regimens. Women with higher education, previous antibiotic use experience, and very easy accessibility to primary doctors were more likely to have high antibiotic knowledge than those with primary education, no antibiotic use in the previous year, and easy/other level of accessibility to primary doctors. Subjects residing in urban areas and with less accessibility to primary doctors were more likely to self-medicate with antibiotics. Additionally, the completion of antibiotic regimens was positively associated with access to a primary care doctor and high antibiotic knowledge. Conclusion: IF Policymakers tend to reduce inappropriate antibiotic use among women. Priority advocates are recommended for urban residents who have experiences of antibiotic use in the previous year. It is therefore important to increase their awareness, particularly regarding diseases against which antibiotics are effective, and activities such as unnecessary use of antibiotics in healthy animals, which may affect their overall effectiveness among humans. More communication channels should be included in the overall scheme to improve the public awareness and accessibility of health professionals.